Urban and long-range driving cycle for electric vehicle: a review - Syed Mohd Azizi, Syed Muhammad Aslam; Mohd Razin, Muhammad Aiman; Toha, Siti Fauziah; Malik, Hafizi; Idris, Ahmad Syahrin (Perintis Malaysia, 2023)
Electric vehicles (EV) according to the definition given by German government and the National Development Plan of Electric Mobility (NEP) consist of all road vehicles that are supplied by an electric motor and particularly get their energy from the power grid which can be recharged externally. There are three types of EV included which are the Range Extended Electric Vehicles (REEV), Plug-in Hybrid Electric Vehicles (PHEV), and the purely electric vehicles (EV). The performance of EV such as the energy and power consumption, and emission can be determined by the means of drive cycles just like for the conventional vehicles. In this paper, the methodology for the development of drive cycles is explained in detail. There are hundreds or even thousands of drive cycles developed all over the world either legislative or non-legislative. We will also be discussing about some of the prominent driving cycles used by international organizations such as the Environmental Protection Agency (EPA) and California Air Research Board (CARB). A total of 15 drive cycles will be covered in this paper covering the rural, urban, and highway areas. The drive cycles are INRETS drive cycle, Indian drive cycle, Manhattan drive cycle, Urban Dynamometer Driving Schedule (UDDS), Representative Non-LA4 (REP05) drive cycle, Highway Fuel Economy Test (HWFET) drive cycle, US06 drive cycle, SC03 drive cycle, BUSTRE drive cycle, ARB02 drive cycle, CLEVELAND drive cycle, Japanese 10-15 mode drive cycle, ECE drive cycle, EUDC, and New European Drive Cycle (NEDC). Heavy duty electric vehicles such as buses are also considered in this paper. For instance, the Manhattan drive cycle is included to represent the driving pattern of buses.